Cysteine Boosts Fitness Under Hypoxia-Mimicked Conditions in Ovarian Cancer by Metabolic Reprogramming - Nunes, Sofia C. (2021)
Funding Information: Funding. This research was supported by Funda??o para a Ci?ncia e Tecnologia (FCT) (Ph.D. ProRegeM program, Ref: PD/BD/105893/2014; FCT individual Ph.D. fellowship Ref: 2020.06956.BD) and iNOVA4 Health (Project 4 and Project 21). iNOVA4Health-UID/Multi/04462/2013 is a program financially supported by Funda??o para a Ci?ncia e Tecnologia/ Minist?rio da Educa??o e Ci?ncia, through national funds. The authors would like to acknowledge the Instituto Portugu?s de Oncologia de Lisboa Francisco Gentil (IPOLFG) for partially funding the project. Publisher Copyright: © Copyright © 2021 Nunes, Ramos, Santos, Mendes, Silva, Vicente, Pereira, Félix, Gonçalves and Serpa.